The usage of whatsapp application as an internal communication medium using technology acceptance model (TAM) at ALAM Maritim Sendirian Berhad (AMSB) - Ramly, Rustam Kamal (2022)
The assessment on the usage of WhatsApp in daily communications is the central assessment of this study. This study aimed to examine the relationship between the. usability, ease to use, behavioral of user as well as the intention of usage for such application in determining its effective as internal communication in Alam Maritim Sendirian Berhad. The research used Technology Acceptance Model (TAM) as the main framework of the research. The sample used in this research consists of 130 employees of AMSB. Based on the findings, all the variables under TAM model, have a positive and strong relationship with the overall regression model. In this case, the analysis showed that the independent variables statistically significantly predict the dependent variable which indicated that the regression model is a good fit of the data.